Determining Factors of Sharia General Insurance Profitability: Study on Investment Returns, Premiums and Operating Expenses - Herawati, Mesi; Khusni, Kholilatul; Novita, Yeyen (Disclosure: Journal of Accounting and Finance, 2025)
This research aims to analyze the influence of investment returns, premium income and operating expenses on the profitability of sharia general insurance companies in Indonesia. The research method used is quantitative with multiple regression analysis. The data used in this research is secondary data taken from the financial reports of sharia general insurance companies in Indonesia. Data processing was carried out using the EViews 12 application. The research results show that investment returns have a significant effect on the profitability of sharia general insurance in Indonesia. However, partially, premium income and operating expenses do not have a significant effect on profitability. However, when analyzed simultaneously, the variables of investment returns, premium income and operating expenses together have a significant influence on the profitability of sharia general insurance companies. These findings indicate that sharia insurance companies need to focus on efficient investment management to increase profitability. In addition, although premium income and operating expenses do not have a partially significant effect, good management of these two variables in combination with investment returns can have a significant impact on the company's financial performance.